Analysis of Changes in the Stipulation of the Employment Creation Law on Taxation Laws - Abd Rohman Taufiq; Siami Romadhini (Politeknik Negeri Madiun, 2022)
This study aims to determine the changes in taxation legislation based on the determination of the work copyright law in 2021. This study uses a literature review study method with a normative juridical approach. The object of the research was the Danny Darusslam Tax Center. The data source used is secondary data. Technical analysis of data by using a matrix of changes in income tax laws. The results of the study explain that the Job Creation Act was passed to help the country's economic recovery by simplifying, synchronizing and trimming laws and regulations, especially in the field of taxation in order to attract investors. In addition, the Job Creation Law to increase investment funding is regulated in Law Number 2 of 2020, encouraging taxpayer compliance and voluntary payment, increasing legal certainty, and creating justice by taxing electronic transactions.